2015
DOI: 10.1097/gox.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Interacts with Ischemia in a Synergistic Way on Wound Repair and Myofibroblast Differentiation

Abstract: Background:Hyperglycemia is known to adversely affect the outcome of ischemic insults, but its interaction with ischemia has not been investigated in wound repair yet. In this study, we develop a new animal model allowing to investigate the interaction between hyperglycemia and ischemia during the wound repair process. We focus on myofibroblast differentiation, a key element of wound repair.Methods:Ischemia was inflicted in Wistar rats by resection of the femoral to popliteal arteries on the left side, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
4
14
0
2
Order By: Relevance
“…In addition, hypoproteinemia can lead to decreased anti-infective capacity of injured tissue ( 28 ). Of course, excessive protein intake can also have a negative impact because hyperglycemia can increase the burden on organs and then delay in tissue repair ability occurs ( 29 , 30 ). In this study, in addition to healing time and pressure ulcer area of the two indicators, H&E staining result also proved the above view point.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoproteinemia can lead to decreased anti-infective capacity of injured tissue ( 28 ). Of course, excessive protein intake can also have a negative impact because hyperglycemia can increase the burden on organs and then delay in tissue repair ability occurs ( 29 , 30 ). In this study, in addition to healing time and pressure ulcer area of the two indicators, H&E staining result also proved the above view point.…”
Section: Discussionmentioning
confidence: 99%
“…14 17 18 Alizadeh et al 14 reported that the wound was completely closed by day 17 in all animals within the non-ischemic group as compared with day 27 in the ischemic group. Tobalem et al 17 18 reported that non-ischemic wounds closed in a mean of 27.3±3.1 days as compared with 33.4±7.6 days for ischemic wounds (p=0.002) under normoglycemic condition. The meta-analysis showed that ischemia significantly delayed the time to full wound closure (SMD=1.97 (95% CI 1.59 to 2.34)) (online supplementary figure 4).…”
Section: Effect Of Ischemia On Complete Wound Closurementioning
confidence: 96%
“…Of 5844 screened studies, a total of 7 were included (online supplementary figure 1). [14][15][16][17][18][19][20]…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Лечение гнойно-некротических форм диабетической стопы предусматривает многократные хирургические вмешательства и, как следствие, многократное анестезиологическое обеспечение [11]. Обезболивание является необходимым компонентом хирургического лечения пациента, которое, с одной стороны защищает организм от хирургической агрессии, а с другой, влияет на системы жизнеобеспечения, подвергая пациента на риск возможных осложнений [17,20]. Наличие полиорганной патологии, характерной для данного заболевания, предъявляет повышенные требования, прежде всего к безопасности анестезии с минимальным влиянием на углеводный обмен и функции центральной нервной системы (ЦНС) [10], необходимости сохранения сознания больного во время вмешательства с целью диагностики или мониторинга функций ЦНС [2,7].…”
unclassified